1993
DOI: 10.1111/j.1600-0447.1993.tb03398.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective data on the prevalence of abnormal involuntary movements among elderly people living in the community

Abstract: Trained raters from the Liverpool Continuing Health in the Community study interviewed 1070 people over the age of 65 in 1982-1983 using the Geriatric Mental State (GMS) examination. Three years later the cohort was re-interviewed, this time by psychiatrists trained in the GMS, who used the GMS and the History and Aetiology Schedule (HAS). The cohort had fallen in size to 875, because of mortality; 701 were re-interviewed. The cohort was followed up again 6 years after the first interview by trained nurse rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Thus, the study appears to be unique and is not strictly comparable with the extant literature. Some studies have addressed movement disorder prevalences in special populations incomparable to that of the present study, including children (Richardson et al 1991), patients with particular diagnoses such as mental retardation (Rao et al 1987) or affective disorders (Ghadirian et al 1996), patients on specific drugs (multiple studies), and normal community populations (Green et al 1993). Second, patients were referred for evaluation of suspected TD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, the study appears to be unique and is not strictly comparable with the extant literature. Some studies have addressed movement disorder prevalences in special populations incomparable to that of the present study, including children (Richardson et al 1991), patients with particular diagnoses such as mental retardation (Rao et al 1987) or affective disorders (Ghadirian et al 1996), patients on specific drugs (multiple studies), and normal community populations (Green et al 1993). Second, patients were referred for evaluation of suspected TD.…”
Section: Discussionmentioning
confidence: 95%
“…Other prevalence studies have looked at the sequelae of individual drugs. Still other studies have considered the prevalence of movement disorders in community samples not selected for psychiatric disorders (Green et al 1993). In the present study, drug-induced parkinsonism was quite common, followed by dystonia and akathisia, which is similar to results seen in a sample of 1,107 psychiatric patients (Grohmann et al 1990), despite methodological differences.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have also explored the link between cognitive impairment and T D (Green et a/., 1993;Karson et al, 1990Karson et al, , 1993Wragg and Jeste, 1988). Karson et al (1993) found that TD was associated with cognitive impairment in seven domains in older psychiatric patients who were not diagnosed specifically with an organic mental disorder.…”
mentioning
confidence: 96%